Legal, Library, and Accounting Barriers of e-Books for e-Learning during COVID-19 at Polytechnic in Pozega (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
The sudden and rapid appearance of COVID-19 surprised many, so the whole world switched to the digital environment at one point. Business meetings, classes, and social events took place via the Internet. In such an environment, e-books have played a major role in responding to distance learning. But the e-book is still a novelty in both the library and accounting businesses. In this paper, we will give an overview of legal, technical, library, and accounting issues that e-book brings and try to answer how to solve them and how to ensure the availability of e-books in the long term. We will also show how this affected students in the learning process.